Method for purifying quartz sand through calcination and water quenching

Through calcining water quenching and polyvinyl alcohol gel treatment, combined with vacuum adsorption, the problem of difficult removal of gas-liquid inclusions in quartz sand is solved, the purity and transparency of quartz sand is improved, and the efficient purification effect is achieved.

CN119240714AActive Publication Date: 2025-01-03NANTONG ZHIYU QUARTZ MATERIAL CO LTD

Patent Information

Application Number
CN202411489437.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-03
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove impurities of micro-to-nano-scale gas-liquid inclusions in quartz sand, resulting in primary problems and obstacles to domestic substitution in the production of high-purity quartz sand.

Method used

The quartz sand is heated to 1200-1300℃ by calcining water quenching method, and then quenched with 0-70℃ pure water. By forming polyvinyl alcohol hydrogel and aerogel, combined with vacuum adsorption treatment, the gas liquid in the quartz sand is removed. Inclusions and other impurities.

Benefits of technology

It significantly improves the purification accuracy and removal rate of quartz sand, enhances the purity of quartz sand, reduces the metal impurity content, and improves the transparent layer thickness and clarity of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099611110000131
    Figure BDA0005099611110000131
  • Figure BDA0005099611110000132
    Figure BDA0005099611110000132
  • Figure BDA0005099611110000141
    Figure BDA0005099611110000141
Patent Text Reader

Abstract

The invention discloses a method for purifying quartz sand through calcination and water quenching, and belongs to the technical field of deep purification processing of quartz sand, and the method comprises the following steps: carrying out calcination and water quenching on the quartz sand, heating the quartz sand to 1200-1300 DEG C for calcination during calcination and water quenching, and then carrying out water quenching with 0-70 DEG C purified water; during calcination and water quenching, the particle size of the quartz sand is 0.05-0.15 mm. According to the method, the calcining temperature of the quartz sand is increased, the temperature difference during water quenching is increased, and the quartz sand with proper particle size is matched for calcining and water quenching, so that the quartz sand can be promoted to burst to form more cracks and stress concentration, and the removal rate of gas-liquid inclusions in the quartz sand is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of deep purification and processing of quartz sand, in particular to a method for purifying quartz sand by calcining and water quenching. Background Art

[0002] In addition to the well-known metal elements, harmful impurities in quartz sand include micron or even nano-scale gas-liquid inclusions, which are not only ubiquitous but also more difficult to remove. This has become the primary problem in the production of high-purity quartz sand worldwide today, and is also the main difficulty hindering my country's high-purity quartz sand from truly achieving domestic substitution of raw materials and products.

[0003] In order to remove gas-liquid inclusion impurities in high-purity quartz sand, researchers and production companies in my country have proposed and practiced a variety of process methods including calcination and water quenching, flotation, microwave high-temperature explosion, etc. in recent years, but they have achieved little success in actual production applications.

[0004] For example, in the invention patent application with publication number CN115367763 A, “A high-temperature cyclic treatment and preparation process for high-purity quartz sand”, the quartz sand is repeatedly heated and cyclically treated in the temperature range of 1000-1500°C and 600-950°C for multiple times, which can cause the quartz sand to change in volume and promote the enrichment of lattice impurities on the surface of the quartz sand under the effect of recrystallization; however, multiple treatments at too high a temperature will cause adhesion between the particles of the quartz sand, resulting in a reduction in the removal effect of the gas-liquid inclusions, and the process method of multiple high-temperature cyclic treatments is complicated and difficult to operate. For example, in the invention patent application with publication number CN 105036545A, “A process for removing gas-liquid inclusions in high-purity quartz sand”, high-purity quartz sand is subjected to microwave radiation treatment, and the microwave power is 1000-4000w, the radiation treatment time is 1-10h, and the high-purity quartz sand is processed in one time with 100-600g; this method uses microwave radiation technology for treatment, which is difficult to operate, has high requirements on equipment, and has limited single processing capacity, which is difficult to meet the large-scale practical needs of industry.

[0005] At present, the entire industry still relies on finding ore raw materials with very little gas-liquid inclusion content, and is basically completely dependent on imports. Summary of the invention

[0006] The object of the present invention is to provide a method for calcining and water-quenching purifying quartz sand to solve the problems raised in the above background technology.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for calcining and quenching quartz sand for purification, comprising the following steps:

[0008] The quartz sand is calcined and water quenched, wherein the quartz sand is heated to 1200-1300° C. and calcined, and then quenched with 0-70° C. pure water;

[0009] During calcination and water quenching, the particle size of the quartz sand is 0.05-0.15 mm.

[0010] Furthermore, before calcining and water quenching the quartz sand, it is firstly subjected to pretreatment, wherein the pretreatment includes one or more of hand selection, crushing and classification, weak magnetic separation, flotation, pickling, ultrasonic cleaning, dehydration and drying.

[0011] Furthermore, a 7-15wt% polyvinyl alcohol aqueous solution is prepared with pure water above 95°C, and quartz sand that has been calcined and quenched with water is added to the polyvinyl alcohol aqueous solution to form a sol. After multiple freeze-thaw cycles, a quartz sand-hydrogel system is formed; after drying, a quartz sand-aerogel system is obtained; the quartz sand-aerogel system is subjected to vacuum adsorption treatment; and finally, the aerogel on the surface of the quartz sand is removed.

[0012] Furthermore, the drying method is vacuum drying or supercritical drying.

[0013] Furthermore, the drying conditions of the supercritical carbon dioxide drying are: pressure 7.5-11 MPa, temperature 35-40° C., and drying time 9-12 h.

[0014] Furthermore, during the vacuum adsorption treatment, the quartz sand-aerogel system is firstly mechanically crushed to form particles of 0.1-0.3 mm, and then placed in a vacuum environment of 0.1-0.2 Pa and allowed to stand for adsorption for 10-20 hours.

[0015] Furthermore, after the vacuum adsorption treatment, the quartz sand-aerogel system is taken out and added into a large amount of pure water above 95° C., and ultrasonically treated to dissolve the polyvinyl alcohol and then discharged.

[0016] Furthermore, after the pure water treatment, the quartz sand is then leached with mixed acid, wherein the mixed acid includes one or more of sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid, and oxalic acid.

[0017] Furthermore, the polyvinyl alcohol is a low molecular weight polyvinyl alcohol with a molecular weight of 20,000-35,000.

[0018] Compared with the prior art, the method of calcining and water quenching to purify quartz sand of the present invention has the following beneficial effects:

[0019] The present invention firstly increases the calcination temperature of quartz sand, increases the temperature difference during water quenching, and performs calcination and water quenching with quartz sand of suitable particle size, which can promote the quartz sand to burst to form more cracks and stress concentration, and improve the removal rate of gas-liquid inclusions in the quartz sand.

[0020] In the present invention, polyvinyl alcohol hydrogel is further formed by in-situ coating on the surface of quartz sand, which is dried to form aerogel, and then subjected to vacuum adsorption treatment. The high adsorption characteristics of the aerogel are utilized to fully adsorb impurities in the quartz sand, thereby greatly improving the purification accuracy of the quartz sand. In addition, the polyvinyl alcohol is easy to remove and will not bring in other impurities. DETAILED DESCRIPTION

[0021] The present invention provides a quartz sand purification method, comprising the following steps:

[0022] (I) Pre-treatment

[0023] The pre-treatment methods include hand selection, crushing and classification, weak magnetic separation, flotation, pickling, ultrasonic cleaning, dehydration, drying and other methods.

[0024] The specific operation steps of the pre-treatment can refer to the existing technology, such as the relevant technical means in the invention patent applications with publication numbers CN115849393A, CN101337767A, etc., which will not be repeated here.

[0025] (ii) Calcination and water quenching

[0026] Quartz sand with a particle size of 0.05-0.15mm is screened, heated to 1200-1300℃ for calcination, and then quenched with 0-70℃ pure water to promote the explosion of quartz sand, form cracks, and release gas-liquid inclusions.

[0027] In the present invention, the calcination and water quenching process can be carried out continuously. First, the electric furnace is turned on and preheated to a set temperature, and then the material can be continuously fed, calcined through a loading quartz tube (or silicon carbide ceramic tube), and the material can be water quenched.

[0028] When calcining quartz sand, it was found that when the calcination temperature was higher than 1300°C, the quartz sands adhered to each other and formed a certain agglomeration. After water quenching, not only could the original gas-liquid inclusions not be removed, but new gas-liquid inclusions and other impurities were introduced. When the calcination temperature was lower than 1200°C, the temperature difference during water quenching was low, and it was impossible to form a maximum explosion to remove the most gas-liquid inclusions. Therefore, the present invention limits the optimal calcination temperature to 1200-1300°C.

[0029] (III) Post-processing

[0030] The calcined and water-quenched quartz sand is transported by a belt elevator, pickled, washed with water, and then dehydrated by a belt vacuum dehydrator (or centrifuge).

[0031] Specifically, the quartz sand is subjected to mixed acid leaching, during which the slurry mass concentration is 8-12%, wherein the mixed acid includes sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid, oxalic acid, etc.; then it is washed with pure water above 95°C, dehydrated, and dried to obtain high-purity quartz sand.

[0032] In a specific preferred embodiment, before post-treatment, the process further includes the steps of in-situ formation of aerogel on the surface of quartz sand and vacuum adsorption:

[0033] (1) Preparation of quartz sand-hydrogel system:

[0034] Prepare a 7-15% polyvinyl alcohol aqueous solution with pure water above 95°C, add calcined quartz sand after water quenching, make the polyvinyl alcohol aqueous solution completely immerse the quartz sand, and form a uniform sol system through ultrasonic dispersion, and fill it into a closed container;

[0035] The above-mentioned sol system is subjected to 3-5 freeze-thaw cycles to form a quartz sand-hydrogel system: first, the sol system is rapidly cooled to -20°C to -25°C, frozen for 20-30 hours, and then taken out and thawed at room temperature 20-25°C. After repeating 3-5 times, a quartz sand-hydrogel system coated with polyvinyl alcohol in situ is formed.

[0036] In the process of forming the quartz sand-hydrogel system, the polyvinyl alcohol solution in the sol state will first penetrate into the cracks or stress concentration areas formed in the quartz sand due to calcination and water quenching. After slow cooling, the polyvinyl alcohol molecular chains will form a network cross-linking in the cracks of the quartz sand. This force will further promote the opening of the cracks or stress concentration areas, which is beneficial to the release of gas-liquid inclusions.

[0037] (2) Preparation of quartz sand-aerogel system:

[0038] The quartz sand-hydrogel system is dried to form a quartz sand-aerogel system in situ coated with polyvinyl alcohol.

[0039] The drying method can be vacuum drying or supercritical drying, preferably supercritical carbon dioxide drying: firstly, the quartz sand-hydrogel system is placed in anhydrous ethanol for solvent replacement, during which the anhydrous ethanol is replaced several times, once every 6-12 hours, and after 3-5 times of replacement, an alcohol gel is formed; then the alcohol gel is dried by supercritical carbon dioxide, and the drying conditions are: pressure 7.5-11MPa, temperature 35-40°C, and drying time 9-12h. A quartz sand-aerogel system is obtained.

[0040] During supercritical carbon dioxide drying, the carbon dioxide in a supercritical state will penetrate into all pores in the quartz sand-hydrogel system, bringing out the residual gas, liquid or gas-liquid inclusions in the quartz sand, thereby improving the purification effect.

[0041] (3) Vacuum adsorption treatment:

[0042] The quartz sand-aerogel system is mechanically crushed into 0.1-0.3 mm particles, placed in a vacuum environment of 0.1-0.2 Pa, and left to stand for 10-20 hours. The polyvinyl alcohol aerogel has a huge specific surface area and surface energy, and has a strong adsorption capacity. The vacuum treatment can avoid interference from other substances, further promoting the polyvinyl alcohol aerogel to adsorb residual gases, liquids, gas-liquid inclusions and other micro impurities in the quartz sand. Other micro impurities include molecules, ions, etc., such as Al 3+ , K + 、Na + , Ca 2+ Mg 2+ 、Ti 4 + Metal ion impurities.

[0043] (4) Removal of impurities:

[0044] The quartz sand-aerogel system after vacuum adsorption treatment is added into a large amount of pure water above 95°C, and ultrasonically treated to dissolve the polyvinyl alcohol and then discharge it.

[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] This embodiment uses a "box-type double-tube bottom discharge high-temperature calcining water quenching furnace" as the test equipment. The electric furnace loading tubes are two parallel high-purity silicon carbide ceramic tubes with an outer diameter of 300 mm, an inner diameter of 280 mm, and a total length of 5700 mm. The silicon carbide ceramic tube is closed from the inside at a distance of 500 mm from the tail, and four 30×50 mm discharge holes are opened in the front close to the closed position. Quartz sand is discharged from these four small holes. The equipment uses silicon carbon rod heating with a power of 180KW. The height difference between one end of the feed port and the discharge port is about 150mm. The motor drives the roller, and the roller drives the silicon carbide ceramic tube to rotate slowly at a speed of 5-6rpm, driving the quartz sand to roll slowly toward the discharge port. After reaching the discharge hole, it falls into the quartz glass water tank tightly attached below and is immediately submerged in 0-70℃ pure water for water quenching.

[0048] This embodiment uses high-quality quartz ore imported from India as raw material and purifies it through the following steps:

[0049] Quartz sand samples with a particle size range of 0.05-0.15mm are produced through hand selection, crushing and grading, weak magnetic separation, flotation, mixed acid leaching in reactor, pure water cleaning in ultrasonic cleaning machine, dehydration and drying.

[0050] Add the quartz sand sample after pretreatment and particle size screening into the electric furnace, turn on the electric furnace, preheat to the target working temperature of 1250°C, calcine for 2 hours after the electric furnace reaches the set working temperature, and turn on the pure water switch before the quartz sand flows out of the loading tube to ensure that the quartz sand flowing out of the loading tube after calcination is promptly saturated and quenched with 0-70°C pure water.

[0051] Then the quartz sand product after calcination and water quenching is dehydrated by a centrifuge, dried in a box-type quartz tube electric furnace at 600℃, and cooled in a quartz tube cooler.

[0052] Then, the quartz sand is leached with mixed acid. During leaching, the slurry concentration is 10%, and the mixed acid includes 10% sulfuric acid, 10% hydrochloric acid, and 10% oxalic acid; then it is ultrasonically cleaned, dehydrated, and dried with pure water above 95°C to obtain high-purity quartz sand.

[0053] Example 2

[0054] This embodiment uses a "box-type double-tube bottom discharge high-temperature calcining water quenching furnace" as the test equipment. The electric furnace loading tubes are two parallel high-purity silicon carbide ceramic tubes with an outer diameter of 300 mm, an inner diameter of 280 mm, and a total length of 5700 mm. The silicon carbide ceramic tube is closed from the inside at a distance of 500 mm from the tail, and four 30×50 mm discharge holes are opened in the front close to the closed position. Quartz sand is discharged from these four small holes. The equipment uses silicon carbon rod heating with a power of 180KW. The height difference between one end of the feed port and the discharge port is about 150mm. The motor drives the roller, and the roller drives the silicon carbide ceramic tube to rotate slowly at a speed of 5-6rpm, driving the quartz sand to roll slowly toward the discharge port. After reaching the discharge hole, it falls into the quartz glass water tank tightly attached below and is immediately submerged in 0-70℃ pure water for water quenching.

[0055] This embodiment uses high-quality quartz ore imported from India as raw material and purifies it through the following steps:

[0056] Quartz sand samples with a particle size range of 0.05-0.15mm are produced through hand selection, crushing and grading, weak magnetic separation, flotation, mixed acid leaching in reactor, pure water cleaning in ultrasonic cleaning machine, dehydration and drying.

[0057] The quartz sand sample after pretreatment and particle size screening is added into the electric furnace, which is turned on and preheated to the target working temperature of 1200°C. After the electric furnace reaches the set working temperature, it is calcined for 2 hours. Before the quartz sand flows out of the loading tube, the pure water switch is turned on to ensure that the quartz sand flowing out of the loading tube after calcination is promptly saturated and quenched with pure water at 0-70°C.

[0058] Then the quartz sand product after calcination and water quenching is dehydrated by a centrifuge, dried in a box-type quartz tube electric furnace at 600℃, and cooled in a quartz tube cooler.

[0059] Then, a quartz sand-hydrogel system is prepared: a 10% polyvinyl alcohol (molecular weight 20,000) aqueous solution is prepared with pure water above 95°C, and calcined and water-quenched quartz sand is added to make the polyvinyl alcohol aqueous solution completely immerse the quartz sand, and a uniform sol system is formed by ultrasonic dispersion, which is then filled into a sealed container;

[0060] The above sol system was subjected to three freeze-thaw cycles to form a quartz sand-hydrogel system: first, the sol system was rapidly cooled to -20°C, frozen for 20 hours, and then taken out and thawed at room temperature 20-25°C. After repeating this three times, a quartz sand-hydrogel system in situ coated with polyvinyl alcohol was formed.

[0061] The quartz sand-hydrogel system is subjected to supercritical drying: first, the quartz sand-hydrogel system is placed in anhydrous ethanol for solvent replacement, and the solvent is replaced every 6-12 hours. After 3-5 replacements, an alcohol gel is formed; then the alcohol gel is dried by supercritical carbon dioxide, and the drying conditions are: pressure 10MPa, temperature 38°C, and drying time 10h, to form a quartz sand-aerogel system in situ coated with polyvinyl alcohol.

[0062] The quartz sand-aerogel system was mechanically crushed into particles of 0.1-0.3 mm, placed in a vacuum environment of 0.1-0.2 Pa, and allowed to stand for 15 h for vacuum adsorption to remove impurities.

[0063] The quartz sand-aerogel system after vacuum adsorption treatment is added into a large amount of pure water above 95°C, and ultrasonically treated to dissolve the polyvinyl alcohol and then discharge it.

[0064] Then, the quartz sand is leached with mixed acid. During leaching, the slurry concentration is 10%, and the mixed acid includes 10% sulfuric acid, 10% hydrochloric acid, and 10% oxalic acid; then it is ultrasonically cleaned, dehydrated, and dried with pure water above 95°C to obtain high-purity quartz sand.

[0065] Example 3

[0066] This embodiment uses a "box-type double-tube bottom discharge high-temperature calcining water quenching furnace" as the test equipment. The electric furnace loading tubes are two parallel high-aluminum quartz glass tubes with an outer diameter of 220 mm, an inner diameter of 200 mm, and a total length of 6500 mm. The quartz glass tube is closed from the inside at a distance of 550 mm from the tail, and 4 30×40 mm discharge holes are opened in the front close to the closed position. Quartz sand is discharged from these 4 small holes. The equipment uses silicon carbon rod heating with a power of 160KW. The height difference between one end of the feed port and the discharge port is about 150mm. The motor drives the roller, and the roller drives the quartz glass tube to rotate slowly at a speed of 5-6rpm, driving the quartz sand to roll slowly toward the discharge port. After reaching the discharge hole, it falls into the quartz glass water tank tightly attached below and is immediately submerged in 0-70℃ pure water for water quenching.

[0067] This embodiment uses high-quality quartz ore imported from India as raw material and purifies it through the following steps:

[0068] Quartz sand samples with a particle size range of 0.05-0.15mm are produced through hand selection, crushing and grading, weak magnetic separation, flotation, mixed acid leaching in reactor, pure water cleaning in ultrasonic cleaning machine, dehydration and drying.

[0069] The quartz sand sample after pretreatment and particle size screening is added into the electric furnace, which is turned on and preheated to the target working temperature of 1300°C. After the electric furnace reaches the set working temperature, it is calcined for 1.5 hours. Before the quartz sand flows out of the loading tube, the pure water switch is turned on to ensure that the quartz sand flowing out of the loading tube after calcination is promptly saturated and quenched with pure water at 0-70°C.

[0070] Then the quartz sand product after calcination and water quenching is dehydrated by a centrifuge, dried in a box-type quartz tube electric furnace at 600℃, and cooled in a quartz tube cooler.

[0071] Then, a quartz sand-hydrogel system was prepared: a 10% polyvinyl alcohol (molecular weight 22,000) aqueous solution was prepared with pure water above 95°C, and calcined and water-quenched quartz sand was added to make the polyvinyl alcohol aqueous solution completely immerse the quartz sand, and a uniform sol system was formed by ultrasonic dispersion, which was then filled into a sealed container;

[0072] The above sol system was subjected to 4 freeze-thaw cycles to form a quartz sand-hydrogel system: first, the sol system was rapidly cooled to -25°C, frozen for 18 hours, and then taken out and thawed at room temperature 20-25°C. After repeating this process 4 times, a quartz sand-hydrogel system in situ coated with polyvinyl alcohol was formed.

[0073] The quartz sand-hydrogel system is subjected to supercritical drying: first, the quartz sand-hydrogel system is placed in anhydrous ethanol for solvent replacement, and the solvent is replaced every 6-12 hours. After 3-5 replacements, an alcohol gel is formed; then the alcohol gel is dried by supercritical carbon dioxide, and the drying conditions are: pressure 9.5MPa, temperature 40°C, and drying time 9h, to form a quartz sand-aerogel system in situ coated with polyvinyl alcohol.

[0074] The quartz sand-aerogel system was mechanically crushed into particles of 0.1-0.3 mm, placed in a vacuum environment of 0.1-0.2 Pa, and allowed to stand for 12 h for vacuum adsorption to remove impurities.

[0075] The quartz sand-aerogel system after vacuum adsorption treatment is added into a large amount of pure water above 95°C, and ultrasonically treated to dissolve the polyvinyl alcohol and then discharge it.

[0076] Then, the quartz sand is leached with mixed acid. During leaching, the slurry concentration is 15%, and the mixed acid includes 18% sulfuric acid, 18% hydrochloric acid, and 12% hydrofluoric acid; then it is ultrasonically cleaned, dehydrated, and dried with pure water above 95°C to obtain high-purity quartz sand.

[0077] Example 4

[0078] This embodiment uses a "box-type double-tube bottom discharge high-temperature calcining water quenching furnace" as the test equipment. The electric furnace loading tubes are two parallel high-aluminum quartz glass tubes with an outer diameter of 220 mm, an inner diameter of 200 mm, and a total length of 6500 mm. The quartz glass tube is closed from the inside at a distance of 550 mm from the tail, and 4 30×40 mm discharge holes are opened in the front close to the closed position. Quartz sand is discharged from these 4 small holes. The equipment uses silicon carbon rod heating with a power of 160KW. The height difference between one end of the feed port and the discharge port is about 150mm. The motor drives the roller, and the roller drives the quartz glass tube to rotate slowly at a speed of 5-6rpm, driving the quartz sand to roll slowly toward the discharge port. After reaching the discharge hole, it falls into the quartz glass water tank tightly attached below and is immediately submerged in 0-70℃ pure water for water quenching.

[0079] This embodiment uses high-quality quartz ore purchased from Xinjiang, my country as raw material and purifies it through the following steps:

[0080] Quartz sand samples with a particle size range of 0.05-0.15mm are produced through hand selection, crushing and grading, weak magnetic separation, flotation, mixed acid leaching in reactor, pure water cleaning in ultrasonic cleaning machine, dehydration and drying.

[0081] The quartz sand sample after pretreatment and particle size screening is added into the electric furnace, and the calcination and water quenching operation is carried out in the same electric furnace as in Example 1. The electric furnace is turned on and preheated to the target working temperature of 1250°C. After the electric furnace reaches the set working temperature, it is calcined for 2.5 hours. Before the quartz sand flows out of the loading tube, the pure water switch is turned on to ensure that the quartz sand flowing out of the loading tube after calcination is promptly saturated and soaked in 0-70°C pure water and water quenched.

[0082] Then the quartz sand product after calcination and water quenching is dehydrated by a centrifuge, dried in a box-type quartz tube electric furnace at 600℃, and cooled in a quartz tube cooler.

[0083] Then, a quartz sand-hydrogel system is prepared: a 15% polyvinyl alcohol (molecular weight 30,000) aqueous solution is prepared with pure water above 95°C, and calcined and water-quenched quartz sand is added to make the polyvinyl alcohol aqueous solution completely immerse the quartz sand, and a uniform sol system is formed by ultrasonic dispersion, which is then filled into a sealed container;

[0084] The above sol system was subjected to 5 freeze-thaw cycles to form a quartz sand-hydrogel system: first, the sol system was rapidly cooled to -20°C, frozen for 20 hours, and then taken out and thawed at room temperature 20-25°C. After repeating this process 5 times, a quartz sand-hydrogel system in situ coated with polyvinyl alcohol was formed.

[0085] The quartz sand-hydrogel system is subjected to supercritical drying: first, the quartz sand-hydrogel system is placed in anhydrous ethanol for solvent replacement, and the solvent is replaced every 6-12 hours. After 3-5 replacements, an alcohol gel is formed; then the alcohol gel is subjected to supercritical carbon dioxide drying, and the drying conditions are: pressure 11MPa, temperature 38°C, and drying time 10h, to form a quartz sand-aerogel system in situ coated with polyvinyl alcohol.

[0086] The quartz sand-aerogel system was mechanically crushed into particles of 0.1-0.3 mm, placed in a vacuum environment of 0.1-0.2 Pa, and allowed to stand for 18 h for vacuum adsorption to remove impurities.

[0087] The quartz sand-aerogel system after vacuum adsorption treatment is added into a large amount of pure water above 95°C, and ultrasonically treated to dissolve the polyvinyl alcohol and then discharge it.

[0088] Then, the quartz sand is leached with mixed acid. During leaching, the slurry concentration is 10%, and the mixed acid includes 15% sulfuric acid, 10% hydrochloric acid, 10% oxalic acid and 12% hydrofluoric acid; then it is ultrasonically cleaned, dehydrated and dried with pure water above 95°C to obtain high-purity quartz sand.

[0089] Example 5

[0090] This embodiment uses a "box-type double-tube bottom discharge high-temperature calcining water quenching furnace" as the test equipment. The electric furnace loading tubes are two parallel high-purity silicon carbide ceramic tubes with an outer diameter of 300 mm, an inner diameter of 280 mm, and a total length of 5700 mm. The silicon carbide ceramic tube is closed from the inside at a distance of 500 mm from the tail, and four 30×50 mm discharge holes are opened in the front close to the closed position. Quartz sand is discharged from these four small holes. The equipment uses silicon carbon rod heating with a power of 180KW. The height difference between one end of the feed port and the discharge port is about 150mm. The motor drives the roller, and the roller drives the silicon carbide ceramic tube to rotate slowly at a speed of 5-6rpm, driving the quartz sand to roll slowly toward the discharge port. After reaching the discharge hole, it falls into the quartz glass water tank tightly attached below and is immediately submerged in 0-70℃ pure water for water quenching.

[0091] This embodiment uses high-quality quartz ore imported from India as raw material and purifies it through the following steps:

[0092] Quartz sand samples with a particle size range of 0.05-0.15mm are produced through hand selection, crushing and grading, weak magnetic separation, flotation, mixed acid leaching in reactor, pure water cleaning in ultrasonic cleaning machine, dehydration and drying.

[0093] Add the quartz sand sample after pretreatment and particle size screening into the electric furnace, turn on the electric furnace, preheat to the target working temperature of 1200℃, calcine for 2h after the electric furnace reaches the set working temperature, turn on the pure water switch before the quartz sand flows out of the loading tube, so that the quartz sand flowing out of the loading tube after calcination can be saturated and quenched with 0-70℃ pure water in time.

[0094] Then the quartz sand product after calcination and water quenching is dehydrated by a centrifuge, dried in a box-type quartz tube electric furnace at 600℃, and cooled in a quartz tube cooler.

[0095] Then, a quartz sand-hydrogel system is prepared: a 10% polyvinyl alcohol (molecular weight 20,000) aqueous solution is prepared with pure water above 95°C, and calcined and water-quenched quartz sand is added to make the polyvinyl alcohol aqueous solution completely immerse the quartz sand, and a uniform sol system is formed by ultrasonic dispersion, which is then filled into a sealed container;

[0096] The above sol system was subjected to three freeze-thaw cycles to form a quartz sand-hydrogel system: first, the sol system was rapidly cooled to -20°C, frozen for 20 hours, and then taken out and thawed at room temperature 20-25°C. After repeating this three times, a quartz sand-hydrogel system in situ coated with polyvinyl alcohol was formed.

[0097] The quartz sand-hydrogel system is vacuum dried, wherein the vacuum drying conditions are: drying temperature is 40° C., and drying time is 20 h, to form a quartz sand-aerogel system in situ coated with polyvinyl alcohol.

[0098] The quartz sand-aerogel system was mechanically crushed into particles of 0.1-0.3 mm, placed in a vacuum environment of 0.1-0.2 Pa, and allowed to stand for 15 h for vacuum adsorption to remove impurities.

[0099] The quartz sand-aerogel system after vacuum adsorption treatment is added into a large amount of pure water above 95°C, and ultrasonically treated to dissolve the polyvinyl alcohol and then discharge it.

[0100] Then, the quartz sand is leached with mixed acid. During leaching, the slurry concentration is 10%, and the mixed acid includes 10% sulfuric acid, 10% hydrochloric acid, and 10% oxalic acid; then it is ultrasonically cleaned, dehydrated, and dried with pure water above 95°C to obtain high-purity quartz sand.

[0101] Comparative Example 1

[0102] Compared with Example 1, the difference is that during the calcination and water quenching, the calcination temperature is 900°C.

[0103] Comparative Example 2

[0104] Compared with Example 1, the difference is that the particle size of the quartz sand during calcination and water quenching is 0.25-0.5 mm.

[0105] Comparative Example 3

[0106] Compared with Example 2, the difference is that during the calcination and water quenching, the calcination temperature is 900° C., and the particle size of the quartz sand during the calcination and water quenching is 0.25-0.5 mm.

[0107] Finally, perform a performance test:

[0108] The gas-liquid inclusion content of the quartz sand products obtained in Examples 1-5 and Comparative Examples 1-3 was tested respectively, and the obtained data are shown in Table 1.

[0109] Table 1 Percentage of transparent and non-transparent particles and characteristic categories of gas-liquid inclusions

[0110]

[0111] The quartz sand products obtained from each group were melted into 18-inch arc quartz crucibles, and then the quartz crucibles were sliced. The bubble content and distribution characteristics of the inner layer of the quartz crucible were detected as shown in Table 2.

[0112] Table 2 Quartz crucible transparency performance test

[0113]

[0114]

[0115] At the same time, the percentage (%) content of main metal impurity elements in the treated quartz sand of each group was tested, and the test results are shown in Table 3.

[0116] Table 3 Percentage content of main metal impurity elements in treated quartz sand

[0117]

[0118] The above detection of gas-liquid inclusion characteristics of quartz sand, comparison of transparent layer thickness and bubble content of quartz crucible slices melted from quartz sand, and comparison of detection results of main metal impurity content of quartz sand products all illustrate that the technical scheme of the present invention can very effectively open and remove gas-liquid inclusions of quartz sand, greatly improve the thickness and clarity of the transparent layer of quartz crucible, and also correspondingly reduce the content of main metal impurities in quartz sand products, thereby improving the purity of quartz sand products.

[0119] At the same time, polyvinyl alcohol hydrogel is in situ coated on the surface of quartz sand, and aerogel is formed through supercritical drying. After vacuum adsorption treatment, the high adsorption characteristics of aerogel are utilized to fully adsorb impurities in quartz sand, and gas-liquid inclusions can be further removed to improve the purification accuracy of quartz sand.

[0120] The above embodiments are merely descriptions for the purpose of clearly illustrating the present invention, and are not limitations on the implementation methods. For those skilled in the art, other different forms of changes or modifications may be made based on the above descriptions. It is not necessary and impossible to enumerate all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for calcining and quenching quartz sand, characterized in that: The steps include: The quartz sand is calcined and water quenched, wherein the quartz sand is heated to 1200-1300° C. and calcined, and then quenched with 0-70° C. pure water; During calcination and water quenching, the particle size of the quartz sand is 0.05-0.15 mm.

2. The method for purifying quartz sand by calcining and water quenching as claimed in claim 1, characterized in that: Before calcining and water quenching the quartz sand, it is first pre-treated, which includes one or more of hand selection, crushing and classification, weak magnetic separation, flotation, pickling, ultrasonic cleaning, dehydration and drying.

3. The method for purifying quartz sand by calcining and water quenching as claimed in claim 1, characterized in that: A 7-15wt% polyvinyl alcohol aqueous solution is prepared with pure water above 95°C, and calcined and water-quenched quartz sand is added to the polyvinyl alcohol aqueous solution to form a sol. After multiple freeze-thaw cycles, a quartz sand-hydrogel system is formed; after drying, a quartz sand-aerogel system is obtained; the quartz sand-aerogel system is subjected to vacuum adsorption treatment; and finally, the aerogel on the surface of the quartz sand is removed.

4. The method for calcining and quenching quartz sand as claimed in claim 3, characterized in that: The drying method is vacuum drying or supercritical drying.

5. The method for calcining and quenching quartz sand as claimed in claim 4, characterized in that: The drying conditions of the supercritical carbon dioxide drying are: pressure 7.5-11 MPa, temperature 35-40° C., and drying time 9-12 h.

6. The method for purifying quartz sand by calcining and water quenching as claimed in claim 3, characterized in that: When performing vacuum adsorption treatment, the quartz sand-aerogel system is firstly mechanically crushed to form particles of 0.1-0.3 mm, and then placed in a vacuum environment of 0.1-0.2 Pa and allowed to stand for adsorption for 10-20 hours.

7. The method for purifying quartz sand by calcining and water quenching as claimed in claim 3, characterized in that: After the vacuum adsorption treatment, the quartz sand-aerogel system is taken out and added into a large amount of pure water above 95° C., and ultrasonically treated to dissolve the polyvinyl alcohol and then discharge it.

8. The method for purifying quartz sand by calcining and water quenching as claimed in claim 7, characterized in that: After being treated with pure water, the quartz sand is then leached with mixed acid, wherein the mixed acid includes one or more of sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid, and oxalic acid.

9. The method for purifying quartz sand by calcining and water quenching as claimed in claim 3, characterized in that: The polyvinyl alcohol is a low molecular weight polyvinyl alcohol with a molecular weight of 20,000 to 35,000.

Citation Information

Patent Citations

  • Purification method in process of production of high-pure quartz sand as raw material of quartz glass

    CN101337767A

  • Processes for preparing and purifying quartz sand and quartz powder and products thereof

    CN102070150A

  • Calcination water quenching apparatus for preparing quartz glass raw material-high purity quartz sand

    CN201245546Y

  • Production of quartz glass powder

    JP1995017706A

  • Method of quartz raw material enrichment

    RU2353578C1

Cited By

  • Deep removal method for lattice impurities and inclusions in high-purity quartz sand

    CN120423562A

  • Multi-sensor quartz stone high-temperature water quenching process multi-dimensional parameter optimization system

    CN121739770A